The Politics of Physiognomic Perception - Verstegen Ian (Gestalt Theory, 2022)
This article stages a confrontation between latent nominalist attitudes about inherent expression in perception—physiognomy—and new affective modes. In a classic analysis, Gombrich warned of the lack of veridicality of physiognomic perception, a sentiment endorsed by postmodern theories. At the same time, affect theory affirms a level of directly available intensities. Using the example of Rudolf Arnheim, it can be seen that the two are really specular opposites of each other, each merely valorizing different poles of the affect-cognition scale. Arnheim’s Gestalt theory shows how immediate percepts can have a generic structure, which is differentiated with further acquaintance. Arnheim, however, shows how perception can never account for all the power of expressive seeing. Perception and cognition is always embedded in a social matrix. Using an example of racist antisemitic propaganda used by Gombrich, the political implications of Arnheim’s position are demonstrated.